Current Strategies for the Treatment of Early Stage Osteoarthritis - Ji, Xiuling; Zhang, Hongyu (Frontiers in Mechanical Engineering, 2019)
Osteoarthritis (OA) is a leading cause of disability in elderly individuals. As a common chronic degenerative joint disease, OA is typically characterized by articular cartilage degeneration, subchondral bone sclerosis and concomitant synovium inflammation. As such, the structural and functional alterations in the articular cartilage and subchondral bone become the focus of research during progression of OA. Similarly, the molecular mechanism regulating articular cartilage lubrication and the cellular communication controlling metabolic status of subchondral bone cells promote innovative strategies for prevention and treatment of early stage OA. The current therapeutic options for OA are aimed at keeping the associated pain, inflammation and degeneration of synovial joint tissues manageable in order to minimize the structural and symptomatic progression. These include, but are not limited to, synergetic therapy combining lubrication and drug intervention, regulatory balance between bone resorption and formation, and exercise therapy. In this mini review, we focus on the up-to-date research progress on these novel strategies for OA treatment.